2007
DOI: 10.1002/jbm.a.31082
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐culture period of mesenchymal stem cells in osteogenic media influences their in vivo bone forming potential

Abstract: The objective of this study was to investigate if the in vitro pre-culture period in osteogenic media of rat mesenchymal stem cells (MSCs), influences their ability to regenerate bone when implanted in a critical size cranial defect. MSCs were harvested from the bone marrow of 6-8 weeks old male Fisher rats and expanded in vitro in osteogenic media for different time periods (4, 10, and 16 days) in tissue culture plates (TCP), seeded on sintered titanium fiber meshes without the extracellular matrix (ECM) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
112
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 58 publications
5
112
2
1
Order By: Relevance
“…Preculture period of 4 days has been identified as optimal for bone formation in vivo. 46 The role of fiber diameter on porosity and cell infiltration has also been reported previously. 24 Even though the nanofibers used as osteogenic layers were <100 mm in thickness, cells remained as a single layer above the wafer.…”
supporting
confidence: 59%
“…Preculture period of 4 days has been identified as optimal for bone formation in vivo. 46 The role of fiber diameter on porosity and cell infiltration has also been reported previously. 24 Even though the nanofibers used as osteogenic layers were <100 mm in thickness, cells remained as a single layer above the wafer.…”
supporting
confidence: 59%
“…39 In this study, it was observed that precultured and non-precultured cocultures presented an ALP activity significantly higher than corresponding monocultures. The enhancement of ALP activity in cocultures may be mediated by p38 mitogen-activated protein kinase-dependent stabilization of mRNA for ALP.…”
Section: Discussionmentioning
confidence: 57%
“…however, long-term contact (6 months) between trabecular bonederived cells and natural apatite (anorganic bovine bone) grafted in human maxilla inhibits osteoblast-like phenotype in vitro (24). Further longer pre-culture periods have a critical role in differentiation process for lead to a progressively diminishing of osteoinductivity (25). In this way, the worst performance of the xenograft with cells could be explained by (i) unfavorable adhesion and the challenge to differentiate PDC upon inappropriate material as cell carrier during the experimental period or (ii) inhibition of cellular proliferation and osteoinductive potential due to long pre-culture period in osteogenic media in vitro (6 days) before implantation into an orthotopic site (rcCsD) for in vivo study.…”
Section: Discussionmentioning
confidence: 99%